Beluga whale summer habitat associations in the Nelson River estuary, western Hudson Bay, Canada - Smith, Alexander J. (PLoS One, 2017)
To understand beluga whale (Delphinapterus leucas) estuarine use in the Nelson River estuary, southwest Hudson Bay, we recorded and examined beluga movements and habitat associations for the July through August period in 2002–2005. We compared locations of belugas fitted with satellite transmitters (“tags”) (2002–2005) and aerial-surveyed (2003 and 2005) belugas for years of differing freshwater flow from the Nelson River which is influenced by hydroelectric activity. Using the beluga telemetry location data, we estimated an early August behavioral shift in beluga distribution patterns from local estuarine use to a progressively more migratory behavior away from the estuary. The timing of this shift in behavior was also apparent in results of beluga aerial surveys from the 1940s–1960s, despite environmental changes including later freeze-up and warming ocean temperatures. Overall, during the higher than average discharge (“wet”) year of 2005, the three tagged belugas ranged farther from the Nelson River but not farther from the nearest shore along southwestern Hudson Bay, compared to the 10 tagged belugas tracked during the “dry” years of 2002–2004 with below average discharges. Aerial survey data for 2003 and 2005 display a similar dry vs. wet year shift in spatial patterns, with no significant change in overall density of belugas within the study area. In the Nelson estuary, proximity to the fresh-salt water mixing area may be more important than the shallow waters of the upper estuary. Killer whales (Orcinus orca) were observed in the Churchill area (200 km northwest) during each year of study, 2002–05, and belugas may benefit from the proximity to shallow estuary waters that provide protection from the larger-bodied predator. Study results contribute to an understanding of the influence of environmental variation on how and why belugas use estuaries although considerable uncertainties exist and additional research is required.